2023
DOI: 10.3390/v15091860
|View full text |Cite
|
Sign up to set email alerts
|

Viral Co-Infection in Bats: A Systematic Review

Brent D. Jones,
Eli J. Kaufman,
Alison J. Peel

Abstract: Co-infection is an underappreciated phenomenon in contemporary disease ecology despite its ubiquity and importance in nature. Viruses, and other co-infecting agents, can interact in ways that shape host and agent communities, influence infection dynamics, and drive evolutionary selective pressures. Bats are host to many viruses of zoonotic potential and have drawn increasing attention in their role as wildlife reservoirs for human spillover. However, the role of co-infection in driving viral transmission dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…This intriguing phenomenon is thought to be intricately linked to a combination of ecological and evolutionary traits unique to bats [ 13 , 18 ]. Understanding the interplay between these ecological and evolutionary factors is essential for unravelling the complex dynamics of viral diversity in bat populations [ 19 ]. This underscores the importance of conducting viral research in bats, as it has significant implications not only for public health but also for wildlife conservation and our deeper comprehension of viral evolution [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intriguing phenomenon is thought to be intricately linked to a combination of ecological and evolutionary traits unique to bats [ 13 , 18 ]. Understanding the interplay between these ecological and evolutionary factors is essential for unravelling the complex dynamics of viral diversity in bat populations [ 19 ]. This underscores the importance of conducting viral research in bats, as it has significant implications not only for public health but also for wildlife conservation and our deeper comprehension of viral evolution [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such an overactivation of the immune system not only compromises the individual’s health but also imposes a substantial energy cost. While inflammation is a critical component of the immune response, its excessive and prolonged activation can impose significant physiological costs on vertebrates, potentially compromising vital functions such as the growth, reproduction, and maintenance of homeostasis [ 19 ]. Therefore, it has been hypothesized that through a series of mechanisms associated with bats’ flying abilities they may be able to tolerate viral infection and replication without the excessive inflammation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many sources focused on diseases of bats and their diagnostics, in particular histopathological. Changes were examined during dermatitides (Boone et al, 2021;De Souza Suguiura et al, 2023), diseases of parasitic etiology (Adhikari et al, 2020;Fernandes et al, 2022;Gugnani & Denning, 2023), viral infections (Irving et al, 2021;Kohl et al, 2021;Jones et al, 2023), including paramixovirus (Haas & Lee, 2023), rabies (Folly et al, 2021), and infections of other etiology (Fritze et al, 2019;Colunga-Salas et al, 2021). Mentions of E. serotinus are found only in general reviews of pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the authors found a high frequency of virus co-infection in bats from Yunnan province, which is one of the provinces in China with the highest diversity of animals [13]. In another systematic review, Jones et al reported that viral co-infection in bats is common, although such findings are often ad hoc by-products of viral discovery efforts, instead of results of co-infection studies [14]. Interestingly, it was shown in a recent study using next-generation sequencing that divergent insect-and batassociated viruses, namely densovirus, nodavirus, jingmenvirus, bastrovirus, dicistrovirus, picornavirus and cyclovirus, were detected in the plasma of two individuals from Africa who were enrolled in a blood-borne surveillance program [15].…”
mentioning
confidence: 99%